4, 5-seco-Probotryenols A–C, a new type of sesquiterpenoids from Stachybotrys bisbyi1. Issue 57 (25th June 2015) - Bao, Yan-Ru; Chen, Guo-Dong; Gao, Hao; He, Rong-Rong; Wu, Yue-Hua; Li, Xiao-Xia; Hu, Dan; Wang, Chuan-Xi; Liu, Xing-Zhong; Li, Yan; Yao, Xin-Sheng
<x xml:space="preserve">Abstract</x> 4, 5-seco-Probotryenols A–C (1–3), a new type of sesquiterpenoids named seco-probotryane-type sesquiterpenoid, have been obtained from Stachybotrys bisbyi, along with five new botryane skeleton sesquiterpenoids (4, 5, and 8–10).